Prevalence, prognosis, and treatment implications of retropharyngeal nodes in unknown primary head and neck carcinoma. (July 2018) - Horowitz, Gilad; Hosni, Ali; Yu, Eugene; Xu, Wei; Lu, Lin; Au, Michael; Dixon, Peter R.; Brown, Dale; Chepeha, Douglas B.; Gilbert, Ralph W.; Goldstein, David P.; Gullane, Patrick J.; et al.
Highlights: Patients with CUP rarely have metastatic disease to the retropharyngeal lymph nodes. In patients with CUP, p16 (−) and radiographic ENE are associated with poor prognosis. It may be possible to de-intensify treatment to the RP in p16 (+) and limited lateral neck nodal disease CUP patients. Abstract: Objective: (1) To estimate the prevalence of radiographically positive Retro-Pharyngeal Lymph Nodes (RPLN) in unknown primary carcinoma of the head and neck and (2) to determine the prognostic implications of radiographically positive RPLN and other radiographic features (3) to identify patients at low risk for retropharyngeal metastasis. Materials and methods: The medical records of all 68 eligible patients treated at the Princess Margaret Cancer Centre between 2000 and 2014 were retrospectively reviewed for demographic, clinical, pathologic, and radiologic data. Radiologic data included: RPLN, extra capsular spread (ECS), neck staging and cystic/necrotic or matted neck nodes. LRR, DR, DFS and OS were estimated using the competing risk methods and the Kaplan-Meier method. Results: Seven patients had concerning RPLN (10.3%). Forty-four patients were p16 positive (65%). RPLN status did not have any effect on LRR, DFS, DR and OS. Radiological ECS and p16 (neg.) status were found to be significant predictors of LRR (p = 0.023; p = 0.014). Matted nodes, radiological ECS and p16 (neg.) status were found to be significant predictors of DFS (p = 0.012; p < 0.001; p = 0.014). Matted nodes and radiological ECS were found to be significant predictors of OS (p = 0.017; p = 0.0036). Only radiological ECS was found to be a significant predictor of distant recurrence (p = 0.0066). Conclusions: 10% of CUP patients will harbor radiological positive RPLN. A large proportion of CUP patients are positive for p16. Radiologic features such as ECS and matted nodes can predict worse outcomes.